Low-temperature oxidation roasting and decarburization process for cryolite in electromagnetic rotary kiln
Patent Information
- Application Number
- CN202611223735.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-13
- Publication Date
- 2026-10-30
AI Technical Summary
然而,目前业内尚未形成适配冰晶石的低温高效除碳成熟工艺,尚无法达到残碳稳定合格与物料高回收率的工业化生产要求
[0022]1、本工艺借助渗透液的渗透与协同氧化作用,可同时脱除冰晶石颗粒表面游离碳及内部包裹的结合碳,解决了传统浮选工艺仅能去除表层碳质、除碳深度不足的缺陷。结合电磁回转窑精准调控的弱氧化气氛焙烧,成品残碳含量可稳定控制在0.11%-0.16%,远低于铝电解原料残碳≤0.5%的行业准入要求,除碳效果显著优于传统高温焙烧工艺,从而有效避免因残碳超标导致的电解槽工况波动与电流效率下降问题。
Smart Images

Figure SMS_12 
Figure SMS_13
Abstract
Description
Technical Field
[0001] This invention relates to the field of cryolite decarbonization technology, specifically to a cryolite electromagnetic rotary kiln low-temperature oxidation roasting decarbonization process. Background Technology
[0002] Cryolite (Na3AlF6) is an indispensable core flux in the aluminum electrolysis industry, which is directly related to the production efficiency and operational stability of aluminum electrolysis. In the process of preparing and reusing cryolite, a large amount of carbon impurities are inevitably introduced. These impurities exist in two forms: free carbon and bound carbon.
[0003] Aluminum electrolysis production has strict requirements for the residual carbon content of raw materials, stipulating that the residual carbon content in the raw materials shall not exceed 0.5%. Once the residual carbon content of cryolite raw materials exceeds the standard, it will directly cause the electrolyte resistance in the electrolytic cell to increase and the conductivity to decrease, resulting in a significant reduction in current efficiency. At the same time, it is very easy to induce repeated occurrences of the anode effect and abnormal fluctuations in the operating conditions of the electrolytic cell, which in turn leads to a series of problems such as the decline in aluminum product quality and the increase in production energy consumption, seriously hindering the stable production of the aluminum electrolysis industry.
[0004] Currently, the main technological methods used in the industry to remove carbonaceous impurities from cryolite include traditional high-temperature roasting in a coal-fired rotary kiln, flotation, and acid leaching purification. However, these methods all have significant shortcomings.
[0005] For example, the traditional coal-fired rotary kiln roasting method suffers from uneven temperature distribution and poor temperature control precision. The temperature difference can typically reach ±100℃ or more, easily leading to localized over-burning, causing cryolite to decompose and volatilize at high temperatures, resulting in the loss of effective components. At the same time, the above process has a roasting time of 3-4 hours, resulting in high energy consumption, low production efficiency, and poor stability in carbon removal, making it difficult to consistently meet the standards for aluminum electrolysis grade raw materials.
[0006] Flotation can only remove free carbon attached to the surface of materials, but cannot separate bound carbon encapsulated inside the materials. The carbon removal depth is insufficient, and the carbon removal qualification rate is low.
[0007] Acid leaching requires a large amount of acid and alkali reagents and generates a large amount of highly acidic wastewater. Environmental treatment costs are high, and the reaction process can easily cause the effective components in the material to dissolve and be lost, reducing the recovery rate of raw materials.
[0008] Electromagnetic rotary kilns are a new type of heating equipment, possessing advantages such as uniform electromagnetic induction heating, precise temperature control, high thermal efficiency, no open flame pollution, and a high degree of automation, enabling precise constant-temperature roasting. However, the industry has not yet developed a mature low-temperature, high-efficiency decarbonization process suitable for cryolite, and it is still unable to meet the industrial production requirements of stable and qualified residual carbon and high material recovery rate.
[0009] Based on this, the present invention designs a cryolite electromagnetic rotary kiln low-temperature oxidation roasting and decarbonization process to solve the above problems. Summary of the Invention
[0010] To address the aforementioned shortcomings of existing technologies, this invention provides a low-temperature oxidation roasting and decarbonization process for cryolite in an electromagnetic rotary kiln, comprising the following steps:
[0011] S1: Permeate is prepared by extracting, filtering and concentrating under reduced pressure using corn cob powder, sodium carbonate, hydrogen peroxide and deionized water as raw materials.
[0012] S2: Ammonium bifluoride, the permeate, and deionized water are mixed and stirred, then sealed and aged to obtain a compound mother liquor;
[0013] S3: Anhydrous aluminum fluoride is mixed and stirred with deionized water, then the compound mother liquor is added and allowed to react fully before aging. The mixture is then filtered to obtain cryolite surface passivation solution.
[0014] S4: After crushing and screening the cryolite raw material to be processed, spray the cryolite surface passivation combination liquid and let it stand. Then send it into an electromagnetic rotary kiln for preheating. After heating, maintain a weak oxidizing atmosphere with an oxygen volume fraction of 8-12% for roasting. After roasting, cool and discharge the material quickly.
[0015] Furthermore, S1 specifically involves: weighing 10-15 parts by weight of 40-60 mesh dried corn cob powder, 2-4 parts by weight of sodium carbonate, 1-3 parts by weight of 25% hydrogen peroxide, and 80-90 parts by weight of deionized water; adding the deionized water to the reaction vessel, adding sodium carbonate and stirring at 120-180 r / min until completely dissolved, heating to 70-85℃ and then adding the corn cob powder, continuing to stir and extract for 2-3 hours; after extraction, filtering to remove the filter residue, collecting the clear filtrate, cooling the filtrate to 60-70℃, adding the hydrogen peroxide and mixing well, and then concentrating under reduced pressure at -0.085MPa to -0.095MPa to 1 / 4-1 / 3 of the original volume to obtain the permeate.
[0016] Furthermore, S2 specifically involves: weighing 6-8 parts by weight of ammonium bifluoride, 1.5-2.5 parts by weight of the permeate, and 10-15 parts by weight of deionized water; adding the deionized water into the reactor, adjusting the rotation speed to 60-90 r / min at room temperature, first adding the permeate and stirring for 5-10 min; adding ammonium bifluoride in 3-4 portions at a temperature not exceeding 35℃, with an interval of 10-15 min between each addition, and continuing to stir for 20-30 min after all additions are completed, then sealing and allowing to stand for aging for 1.5-2.5 h to obtain the compound mother liquor.
[0017] Furthermore, S3 specifically involves: weighing 78-82 parts by weight of deionized water, heating it to 50-60℃, and adjusting the rotation speed to 80-120 r / min; first adding 10-12 parts of anhydrous aluminum fluoride and stirring for 10-15 min, then adding the compound mother liquor in 4-6 portions, with an interval of 12-18 min between each addition; after all the liquor has been added, increasing the rotation speed to 100-150 r / min and continuing to stir for 30-40 min; cooling to room temperature and aging under sealed conditions for 4-6 h; and filtering the aged solution to obtain the cryolite surface passivation combination solution.
[0018] Furthermore, in S4, the cryolite raw material to be processed is subjected to coarse crushing and fine crushing in sequence, and then screened by a double-layer vibrating screen to screen out granular materials with a particle size of 2-5mm; a cryolite surface passivation combination liquid accounting for 1-3% of its mass is sprayed onto the granular material, and after standing for 10-15 minutes, it is transferred to an electromagnetic rotary kiln.
[0019] Furthermore, the material transferred into the electromagnetic rotary kiln is first preheated at 300-400℃ for 20-30 minutes; after preheating, the temperature is raised to 700-750℃, and at the same time, waste heat recovery air at 180-200℃ is injected.
[0020] Furthermore, the rotation speed of the electromagnetic rotary kiln is controlled at 0.8-1.2 r / min, and the roasting treatment is carried out for 1.5-2 hours; after roasting, the material is rapidly cooled to 100℃ before being discharged.
[0021] Compared with the prior art, the beneficial effects of this invention are as follows:
[0022] 1. This process utilizes the penetration and synergistic oxidation effects of the permeating liquid to simultaneously remove free carbon from the surface of cryolite particles and bound carbon encapsulated within them, overcoming the shortcomings of traditional flotation processes that can only remove surface carbon and have insufficient carbon removal depth. Combined with precise control of the weakly oxidizing atmosphere in an electromagnetic rotary kiln, the residual carbon content of the finished product can be stably controlled at 0.11%-0.16%, far below the industry standard of ≤0.5% residual carbon in aluminum electrolysis raw materials. The carbon removal effect is significantly better than traditional high-temperature roasting processes, thus effectively avoiding the problems of electrolytic cell operating fluctuations and current efficiency reduction caused by excessive residual carbon.
[0023] 2. This invention utilizes a cryolite surface passivation solution to form a uniform and dense protective film on the surface of material particles, significantly reducing the damage to the cryolite structure caused by high-temperature roasting and inhibiting fluoride volatilization and material decomposition. The retention rates of fluorine, aluminum, and sodium elements can all reach over 99%, and the main content of the finished product is close to the theoretical composition of cryolite. The material burn-off rate is as low as 0.35%, and the raw material recovery rate is as high as 99.5%, effectively reducing the loss of effective components and significantly improving resource utilization efficiency.
[0024] 3. This process utilizes an electromagnetic rotary kiln to achieve low-temperature roasting at 700-750℃, with a roasting time of only 1.5-2 hours. Compared to the roasting cycle of traditional coal-fired rotary kilns, this significantly shortens the process. Combined with waste heat recovery and air recycling, production energy consumption is significantly reduced. Furthermore, electromagnetic heating provides high temperature control accuracy and a uniform temperature field, eliminating material decomposition problems caused by localized over-burning. Simultaneously, the entire process involves no large-scale input of acid or alkali reagents and generates no highly acidic wastewater, avoiding the high environmental treatment costs associated with acid leaching purification methods. Detailed Implementation
[0025] To make the objectives, technical solutions, and advantages of the embodiments of the present invention clearer, the technical solutions of the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are only some, not all, of the embodiments of the present invention. All other embodiments obtained by those skilled in the art based on the embodiments of the present invention without creative effort are within the scope of protection of the present invention.
[0026] Example 1: This example provides a low-temperature oxidation roasting and decarbonization process for cryolite using an electromagnetic rotary kiln, including the following steps:
[0027] S1: Weigh 10 parts by weight of 40-mesh dry corn cob powder, 2 parts by weight of sodium carbonate, 1 part by weight of hydrogen peroxide (concentration 25%), and 80 parts by weight of deionized water. Add the deionized water to the reaction vessel, add sodium carbonate and stir at 120 r / min until completely dissolved. Then heat to 70℃, add corn cob powder, and continue stirring to extract for 1.5 h. After extraction, filter to remove the residue, collect the clear filtrate, cool the filtrate to 60℃, add hydrogen peroxide in two portions, 15 min apart each time, and keep warm for 1 h to oxidize. Concentrate the oxidized solution under reduced pressure at -0.085 MPa to 1 / 4 of the original volume to obtain the permeate.
[0028] S2: Weigh 6 parts by weight of ammonium bifluoride (purity ≥97%), 1.5 parts by weight of permeate, and 10 parts by weight of deionized water; add the deionized water into the reactor, adjust the speed to 60 r / min at room temperature, add the permeate and stir for 5 min, add the ammonium bifluoride in 3 portions at ≤35℃, with an interval of 10 min between each addition, and continue stirring for 20 min after all the ammonium bifluoride has been added, then seal and let stand for 1.5 h to obtain the compound mother liquor;
[0029] S3: Weigh 78 parts of deionized water by weight, heat to 50℃, adjust the speed to 80r / min, first add 10 parts of anhydrous aluminum fluoride and stir for 10min, then add the compound mother liquor in 4 portions, with an interval of 12min each time. After all the liquor is added, increase the speed to 100r / min and continue stirring for 30min. Cool to room temperature and age under sealed conditions for 4h. The aged solution is filtered through a 0.2μm precision filter to obtain cryolite surface passivation combination solution.
[0030] S4: The cryolite raw material to be processed is subjected to coarse crushing and fine crushing in sequence, and then screened by a double-layer vibrating screen to screen out granular materials with a particle size of 2mm; the 2mm granular materials are sprayed with a cryolite surface passivation combination liquid accounting for 1% of the mass of the granular materials, and left to stand for 10 minutes, and then transferred to an electromagnetic rotary kiln (cryolite feeding speed is 430kg / h) and preheated at 300℃ for 20 minutes.
[0031] After preheating, the temperature is raised to 700℃, and 180℃ waste heat recovery air is injected to maintain a weak oxidizing atmosphere with an oxygen volume fraction of 8% in the kiln.
[0032] The material is calcined for 1.5 hours at a rotation speed of 0.8 r / min in an electromagnetic rotary kiln, and then rapidly cooled to 100°C before being discharged (and sent to a water-cooled spiral cooler for rapid cooling).
[0033] Example 2: This example provides a low-temperature oxidation roasting and decarbonization process for cryolite using an electromagnetic rotary kiln, including the following steps:
[0034] S1: Weigh 15 parts of 60-mesh dry corn cob powder, 4 parts of sodium carbonate, 3 parts of hydrogen peroxide (concentration 25%), and 90 parts of deionized water by weight. Add the deionized water to the reaction vessel, add sodium carbonate and stir at 180 r / min until completely dissolved. Then raise the temperature to 85℃, add the corn cob powder, and continue stirring to extract for 2.5 h. After extraction, filter to remove the filter residue, collect the clear filtrate, cool the filtrate to 70℃, add hydrogen peroxide in 3 portions, 20 min apart each time, and keep warm for 2 h for oxidation. Concentrate the oxidized solution under reduced pressure at -0.095 MPa to 1 / 3 of the original volume to obtain the permeate.
[0035] S2: Weigh 8 parts by weight of ammonium bifluoride (purity ≥97%), 2.5 parts by weight of permeate, and 15 parts by weight of deionized water; add the deionized water into the reactor, adjust the speed to 90 r / min at room temperature, add the permeate and stir for 10 min, add the ammonium bifluoride in 4 portions at ≤35℃, with an interval of 15 min between each addition, and continue stirring for 30 min after all the ammonium bifluoride has been added, then seal and let stand for 2.5 h to obtain the compound mother liquor;
[0036] S3: Weigh 82 parts of deionized water by weight, heat to 60℃, adjust the speed to 120r / min, first add 12 parts of anhydrous aluminum fluoride and stir for 15min, then add the compound mother liquor in 6 portions, with an interval of 18min each time. After all the liquor is added, increase the speed to 150r / min and continue stirring for 40min. Cool to room temperature and age under sealed conditions for 6h. The aged solution is filtered through a 0.5μm precision filter to obtain cryolite surface passivation combination solution.
[0037] S4: The cryolite raw material to be processed is subjected to coarse crushing and fine crushing in sequence, and then screened by a double-layer vibrating screen to screen out granular materials with a particle size of 5mm; the 5mm granular materials are sprayed with a 3% cryolite surface passivation combination liquid by atomization spray, and left to stand for 15min, and then transferred to an electromagnetic rotary kiln (cryolite feeding speed is 470kg / h) and preheated at 400℃ for 30min.
[0038] After preheating, the temperature is raised to 750℃, and 200℃ waste heat recovery air is injected to maintain a weak oxidizing atmosphere with an oxygen volume fraction of 12% in the kiln.
[0039] The material was calcined for 2 hours at a speed of 1.2 r / min in an electromagnetic rotary kiln, and then rapidly cooled to 100°C before being discharged (and sent to a water-cooled spiral cooler for rapid cooling).
[0040] Example 3: This example provides a low-temperature oxidation roasting and decarbonization process for cryolite using an electromagnetic rotary kiln, including the following steps:
[0041] S1: Weigh 12 parts of 50-mesh dry corn cob powder, 3.4 parts of sodium carbonate, 2.6 parts of hydrogen peroxide (concentration 25%), and 86 parts of deionized water by weight. Add the deionized water to the reactor, add sodium carbonate and stir at 160 r / min until completely dissolved. Then heat to 80℃, add corn cob powder, and continue stirring for 2 hours. After extraction, filter to remove the residue, collect the clear filtrate, cool the filtrate to 66℃, add hydrogen peroxide in 3 portions, 17 min apart each time, and keep warm for 2 hours for oxidation. Concentrate the oxidized solution under reduced pressure at -0.095 MPa to 1 / 4 of the original volume to obtain the permeate.
[0042] S2: Weigh 7.2 parts by weight of ammonium bifluoride (purity ≥97%), 2.1 parts by weight of permeate, and 12 parts by weight of deionized water; add the deionized water into the reactor, adjust the speed to 70 r / min at room temperature, add the permeate and stir for 8 min, add the ammonium bifluoride in 4 portions at ≤35℃ with an interval of 12 min between each addition, continue stirring for 25 min after all additions are completed, then seal and let stand for 1.5 h to obtain the compound mother liquor;
[0043] S3: Weigh 80 parts of deionized water by weight, heat to 56℃, adjust the speed to 100r / min, first add 10 parts of anhydrous aluminum fluoride and stir for 15min, then add the compound mother liquor in 5 portions, with an interval of 15min each time. After all the liquor is added, increase the speed to 120r / min and continue stirring for 35min. Cool to room temperature and age under sealed conditions for 5h. The aged solution is filtered through a 0.5μm precision filter to obtain cryolite surface passivation combination solution.
[0044] S4: The cryolite raw material to be processed is subjected to coarse crushing and fine crushing in sequence, and then screened by a double-layer vibrating screen to screen out granular materials with a particle size of 5mm; the 5mm granular materials are sprayed with a cryolite surface passivation combination liquid accounting for 2% of the mass of the granular materials, and left to stand for 15 minutes, and then transferred to an electromagnetic rotary kiln (cryolite feeding speed is 450kg / h) and preheated at 350℃ for 25 minutes.
[0045] After preheating, the temperature is raised to 730℃, and 200℃ waste heat recovery air is injected to maintain a weak oxidizing atmosphere with an oxygen volume fraction of 9% in the kiln.
[0046] The material was calcined for 1.8 hours at a speed of 1.2 r / min in an electromagnetic rotary kiln, and then rapidly cooled to 100°C before being discharged (and sent to a water-cooled spiral cooler for rapid cooling).
[0047] Comparative Example 1: The difference between this comparative example and Example 3 is that, in S4, the cryolite surface passivation solution was not sprayed in.
[0048] Comparative Example 2: The difference between this comparative example and Example 3 is that in S2, the mother liquor was prepared only from ammonium bifluoride and deionized water, and did not contain permeate.
[0049] Comparative Example 3: The difference between this comparative example and Example 3 is that in S2, an equal amount of tea saponin aqueous solution is used instead of the permeate. The tea saponin aqueous solution is made of tea saponin and deionized water in a mass ratio of 20:80.
[0050] Comparative Example 4: This comparative example differs from Example 3 in that the oxygen volume fraction in the kiln is 20%.
[0051] Comparative Example 5: The difference between this comparative example and Example 3 is that the kiln was allowed to cool naturally to room temperature after firing.
[0052] Experimental Example 1: Analyze the residual carbon content (%) after ignition according to GB / T 5124.1-2008.
[0053] Experimental Example 2: The fluorine content (%), aluminum content (%), and sodium content (%) of cryolite prepared by the cryolite electromagnetic rotary kiln low-temperature oxidation roasting and decarbonization process of the present invention were tested according to YS / T 273.17-2020, YS / T 273.4-2020, and YS / T 273.5-2023, respectively.
[0054] Experiment Example 3: Detection of material burn-off rate;
[0055] Weigh 10 kg each of the cryolite granular materials after crushing and screening in Example 1 and Comparative Example 2, and record the total mass of the materials before entering the kiln as follows: ;
[0056] After completing all the steps of this invention, collect all the finished product material after it has been cooled and discharged from the kiln, and weigh its total mass, recording it as follows: The unit is kg;
[0057] Through the formula: Calculate the material burn-off rate.
[0058] Experiment Example 4: Recovery Rate Detection;
[0059] Weigh 10 kg each of the cryolite granular materials after crushing and screening in Example 1 and Comparative Example 2, and record the total mass of the materials before entering the kiln as follows: ;
[0060] After completing all the steps of this invention, collect all the finished product material after it has been cooled and discharged from the kiln, and weigh its total mass, recording it as follows: The unit is kg;
[0061] Through the formula: Calculate the material recovery rate.
[0062] Experimental Example 5: Detection of the retention rates of fluorine, aluminum, and sodium elements;
[0063] The fluorine, aluminum, and sodium contents of the raw materials used in each embodiment and comparative example were measured according to YS / T 273.17-2020 and recorded as follows: The fluorine, aluminum, and sodium content of the finished product after kiln exit is recorded as follows: Record the total mass of materials before they enter the kiln, denoted as . The total mass of the finished product after leaving the kiln is recorded as follows: ;
[0064] Through the formula: Calculate the fluorine retention rate.
[0065] Experimental Example 6: The iron, silicon, phosphorus and titanium content of cryolite prepared by the cryolite electromagnetic rotary kiln low-temperature oxidation roasting and decarbonization process of this invention was tested according to YS / T 273.17-2020.
[0066] The results are shown in Table 1-2;
[0067] Table 1:
[0068]
[0069] Table 2:
[0070]
[0071] As shown in Table 1-2, the theoretical values of cryolite are approximately 54.3% fluorine, 12.9% aluminum, and 32.9% sodium. This invention inhibits high-temperature decomposition through a surface passivation film, so the main contents are close to the theoretical values. The permeate can penetrate deep into the particles to oxidize and bind carbon, and the residual carbon is stably controlled within 0.2%.
[0072] In Comparative Example 1, without surface passivation protection, cryolite underwent severe decomposition and volatilization at high temperatures, resulting in a significant decrease in the main contents and retention rates of fluorine, aluminum, and sodium. Without permeate-assisted oxidation, only surface free carbon could be removed, leaving a residual carbon content as high as 0.32%. The material burn-off rate was 2.6 times that of Example 3, and the recovery rate decreased by 0.8 percentage points, with all core indicators deteriorating.
[0073] The passivation solution in Comparative Example 2 lacked penetrating active components, resulting in poor film uniformity. It could only form a protective layer on the surface of particles and could not remove the internally bound carbon. The residual carbon was twice that of Example 3. The passivation protection effect was reduced, the retention rate of fluorine and sodium decreased by 2-3 percentage points, and the burn-off rate increased by nearly 1 time. The carbon removal effect and material protection were significantly weaker than the complete process.
[0074] Comparative Example 3: Ordinary tea saponin only has surface activity and lacks corn cob extract, so its carbon removal effect is weaker than that of the self-developed permeation solution, and the residual carbon increases to 0.25%; the passivation film has insufficient density, fluorine volatilization is aggravated, and the main content and element retention rate are both lower than those of Example 3, which verifies the irreplaceability of the self-made permeation solution of the present invention.
[0075] While the strong oxidizing atmosphere in Comparative Example 4 can further reduce residual carbon, it will exacerbate the oxidative decomposition of cryolite and the volatilization of fluorides, reducing the fluorine retention rate to 93.1% and the material burn-off rate to as high as 1.2%, resulting in serious loss of effective components. At the same time, the enrichment of impurity elements is more obvious under high temperature and high oxygen conditions, and the iron and silicon content increases, which violates the core objective of low temperature and low loss carbon removal.
[0076] During the furnace cooling process in Comparative Example 5, the stability of the surface passivation film decreased and fluorides continued to volatilize. The carbon-containing flue gas that was not completely discharged from the kiln would re-adhere to the surface of the material during the cooling stage, resulting in a rebound in residual carbon and an increase in burn-off rate. The main content and element retention rate were both lower than those in Example 3 with rapid cooling.
[0077] The above embodiments are only used to illustrate the technical solutions of the present invention, and are not intended to limit it. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art should understand that modifications can still be made to the technical solutions described in the foregoing embodiments, or equivalent substitutions can be made to some of the technical features. Such modifications or substitutions will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.
Claims
1. A low-temperature oxidation roasting and decarbonization process for cryolite in an electromagnetic rotary kiln, characterized in that, Includes the following steps: S1: Permeate is prepared by extracting, filtering and concentrating under reduced pressure using corn cob powder, sodium carbonate, hydrogen peroxide and deionized water as raw materials. S2: Ammonium bifluoride, the permeate, and deionized water are mixed and stirred, then sealed and aged to obtain a compound mother liquor; S3: Anhydrous aluminum fluoride is mixed and stirred with deionized water, then the compound mother liquor is added and allowed to react fully before aging. The mixture is then filtered to obtain cryolite surface passivation solution. S4: After crushing and screening the cryolite raw material to be processed, spray the cryolite surface passivation combination liquid and let it stand. Then send it into an electromagnetic rotary kiln for preheating. After heating, maintain a weak oxidizing atmosphere with an oxygen volume fraction of 8-12% for roasting. After roasting, cool and discharge the material quickly.
2. The cryolite electromagnetic rotary kiln low-temperature oxidation roasting and decarbonization process according to claim 1, characterized in that, S1 is specifically as follows: Weigh 10-15 parts by weight of 40-60 mesh dried corn cob powder, 2-4 parts by weight of sodium carbonate, 1-3 parts by weight of 25% hydrogen peroxide, and 80-90 parts by weight of deionized water; add the deionized water to the reaction vessel, add sodium carbonate and stir at 120-180 r / min until completely dissolved, heat to 70-85℃ and add corn cob powder, continue stirring and extraction for 2-3 hours; after extraction, filter to remove the filter residue, collect the clear filtrate, cool the filtrate to 60-70℃, add the hydrogen peroxide and mix well, then concentrate under reduced pressure to 1 / 4-1 / 3 of the original volume under conditions of -0.085MPa to -0.095MPa to obtain the permeate.
3. The cryolite electromagnetic rotary kiln low-temperature oxidation roasting and decarbonization process according to claim 1, characterized in that, S2 is specifically as follows: Weigh 6-8 parts by weight of ammonium bifluoride, 1.5-2.5 parts by weight of the permeate, and 10-15 parts by weight of deionized water; add the deionized water into the reactor, adjust the rotation speed to 60-90 r / min at room temperature, add the permeate first and stir for 5-10 min; add ammonium bifluoride in 3-4 portions at a temperature not higher than 35℃, with an interval of 10-15 min between each addition, and continue stirring for 20-30 min after all the ammonium bifluoride has been added, then seal and let stand for 1.5-2.5 h to obtain the compound mother liquor.
4. The cryolite electromagnetic rotary kiln low-temperature oxidation roasting and decarbonization process according to claim 1, characterized in that, S3 is specifically as follows: Weigh 78-82 parts of deionized water by weight, heat to 50-60℃, and adjust the speed to 80-120 r / min; first add 10-12 parts of anhydrous aluminum fluoride and stir for 10-15 min, then add the compound mother liquor in 4-6 portions, with an interval of 12-18 min each time; after all the liquor has been added, increase the speed to 100-150 r / min and continue stirring for 30-40 min. After cooling to room temperature, age under sealed conditions for 4-6 h. The aged solution is filtered to obtain the cryolite surface passivation combination solution.
5. The cryolite electromagnetic rotary kiln low-temperature oxidation roasting and decarbonization process according to claim 1, characterized in that, In step S4, the cryolite raw material to be processed is subjected to coarse crushing and fine crushing in sequence, and then screened by a double-layer vibrating screen to screen out granular materials with a particle size of 2-5mm; a cryolite surface passivation combination liquid accounting for 1-3% of its mass is sprayed onto the granular material, and after standing for 10-15 minutes, it is transferred to an electromagnetic rotary kiln.
6. The cryolite electromagnetic rotary kiln low-temperature oxidation roasting and decarbonization process according to claim 5, characterized in that, The material transferred into the electromagnetic rotary kiln is first preheated at 300-400℃ for 20-30 minutes; after preheating, the temperature is raised to 700-750℃, and at the same time, waste heat recovery air at 180-200℃ is injected.
7. The cryolite electromagnetic rotary kiln low-temperature oxidation roasting and decarbonization process according to claim 6, characterized in that, Control the rotation speed of the electromagnetic rotary kiln to 0.8-1.2 r / min, and calcinate for 1.5-2 hours; after calcination, quickly cool to 100℃ and discharge.
